The Moderating Role of Profitability in the Effect of Independent Commissioners and Capital Structure on Firm Value - Ariska, Widi Dwi; Aprilia, Mitha Endah; Poernamawatie, Fahmi; Hastuti, Sri; Rahayu, Laras Puji (Research Horizon, 2025)
The value of a company is a crucial indicator for investors as it reflects management’s effectiveness and future growth prospects. In Indonesia’s manufacturing sector, fluctuations in company value often arise from both governance and financial decisions, making it important to explore internal determinants. This study aims to empirically test whether profitability can moderate the influence of independent commissioners and capital structure on company value. This study uses secondary data from financial reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. There were 84 populations in this study, then based on the criteria, 33 samples were obtained with a research period of 3 years, resulting in 99 samples. The results of this study indicate that profitability can moderate the effect of independent commissioners on company value, but profitability is less able to moderate the effect of capital structure on company value. The results reveal that independent commissioners and capital structure significantly affect company value. Profitability strengthens the effect of independent commissioners but does not moderate the impact of capital structure. These findings highlight the importance of governance effectiveness and financial strategies in enhancing firm value while emphasizing profitability as a catalyst for governance effectiveness.